The Effect of Constructive and Independence Play on Prior Knowledge of Mathematics - Sari, Resti Elma; Budi, Hendri Budi Utama (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study aims to investigate the impact of constructive play and the level of independence on prior knowledge of mathematics. The research method used is experimental. The research findings show that there is an effect of constructive play and the level of independence on early mathematical knowledge. In addition, there is also an interaction between constructive play and the level of independence towards early mathematical knowledge. In the group of children with a high level of independence, the use of Cuisenaire block constructive games resulted in higher initial mathematical knowledge compared to the group of children who were given geometric puzzle constructive games. On the other hand, in the group of children with a low level of independence, the early mathematical knowledge of the children who were given the Cuisenaire block constructive game was lower than the group of children who were given the geometric puzzle constructive game. Therefore, the Cuisenaire block constructive game is suitable for children with a high level of independence, while the geometric puzzle constructive game is more suitable for children with a low level of independence.